DNA damage‐induced apoptosis and mitogen‐activated protein kinase pathway contribute to the toxicity of dronedarone in hepatic cells. (5th February 2018) - Chen, Si; Ren, Zhen; Yu, Dianke; Ning, Baitang; Guo, Lei
Abstract : Dronedarone, an antiarrhythmic drug, has been marketed as an alternative to amiodarone. The use of dronedarone has been associated with severe liver injury; however, the mechanisms remain unclear. In this study, the possible mechanisms of dronedarone induced liver toxicity were characterized in HepG2 cells. Dronedarone decreased cells viability and induced apoptosis and DNA damage in a concentration‐ and time‐dependent manner. Pretreatment of the HepG2 cells with apoptosis inhibitors (caspase‐3, ‐8, and ‐9) or the necrosis inhibitor (Necrox‐5), partially, but significantly, reduced the release of lactate dehydrogenase. Dronedarone caused the release of cytochrome c from mitochondria to cytosol, a prominent feature of apoptosis. In addition, the activation of caspase‐2 was involved in dronedarone induced DNA damage and the activation of JNK and p38 signaling pathways. Inhibition of JNK and p38 by specific inhibitors attenuated dronedarone‐induced cell death, apoptosis, and DNA damage. Additionally, suppression of caspase‐2 decreased the activities of JNK and p38. Dronedarone triggered DNA damage was regulated by downregulation of topoisomerase IIα at both transcriptional and post‐transcriptional levels. Taken together, our data show that DNA damage, apoptosis, and the activation of JNK and p38 contribute to dronedarone‐induced cytotoxicity. Environ. Mol. Mutagen. 59:278–289, 2018. © 2018 Wiley Periodicals, Inc.